Impact of chest pain on mortality in patients with acute pulmonary embolism - Zhang, Jiarui; Zou, Haitao; Tang, Yongjiang; Peng, Lige; Pu, Jiaqi; Zeng, Jiaxin; Chen, Xueqing; Yuan, Jianlin; Yi, Qun; Zhou, Haixia (Scientific reports, 2024)
Evidence for the prognostic impact of chest pain in acute pulmonary embolism (APE) is limited. This study aimed to assess the prognostic value of chest pain in a Chinese cohort of patients with APE. Consecutive hospitalized patients diagnosed with APE between January 2016 and December 2019 were retrospectively enrolled and followed prospectively for 2 years at West China Hospital of Sichuan University. The primary outcome was in-hospital all- cause mortality, while the secondary outcomes included 3-month, 6-month, and 2-year all-cause mortality, APE recurrence, mechanical ventilation, and length of hospital stay (LOS). A total of 737 APE patients met the study criteria, with 254 patients (34.5%) presented with chest pain at admission. Patients with chest pain had significantly lower in-hospital (3.1% vs. 11.2%), 3-month (3.7% vs. 7.5%), 6-month (5.3% vs. 10.0%), and 2-year (9.8% vs. 15.4%) all-cause mortality compared to patients without chest pain (all P < 0.05). A lower rate of mechanical ventilation was observed in APE patients with chest pain, and no significant differences were identified in terms of APE recurrence and LOS between APE patients with and without chest pain. Chest pain was an independent predictor of in-hospital mortality in three separate multivariable models (range of odds ratios 0.390–0.423, all P < 0.05). APE patients with chest pain had a lower short-term and long-term all-cause mortality compared to those without chest pain. Chest pain may be considered a strong, favorable prognostic marker in acute pulmonary embolism.